Conventionalized Language Forms and the Development of Communicative Competence (Eurasian Journal of Humanities and Social Sciences, 2022)
The article corresponds to the current state and prospects for the development of science, in its content it meets the tasks and requirements of modern education, since knowledge of the native and state languages, learning a foreign language expands the horizons of the individual, contributes to its multifaceted development, contributes to the formation of an attitude towards tolerance and a three-dimensional vision of the world. With the entry into the common European home, the question arose in a timely manner of introducing the inhabitant of the coming century to world culture, of bringing his educational level closer to the European standard, of his command of at least two foreign languages. The authors of the Interim State Educational Standard for a Foreign Language put forward an expanded interpretation of the goal of teaching a foreign language in Uzbekistani institutes - the formation of communicative competence.